(untitled) (DARYAFT, 2023)
Mir Beebagar Rind is known as one of the pioneers of resistance and protest in classical Balochi poetry. He actively participated in many battles during the Thirty Years’ War, fought between Rind and Lashars in the fifteenth century. His poetry is a comprehensive account of the wars and battles he fought gallantly. Apart from themes and motifs of resistance and protest, Beebagr’s poetry is also tinged with hues and shades of love and romance. This article primarily discusses various elements of resistance and protest of Mir Beebagr’s poetry.